Photopolymerizable holographic optical element composition

JP2024511267A5Pending Publication Date: 2025-01-07XETOS AG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023548802
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-02-11
Filing Date
2022-02-11
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing photopolymerizable compositions for holograms face challenges in creating thick layers without solvent evaporation issues, require lengthy drying times, and are not suitable for rapid, cost-effective mass production, especially for applications like head-up displays and augmented reality glasses, where unobstructed views are crucial.

Method used

A photopolymerizable composition comprising 25-74.9% monomers with ethylenically unsaturated groups and 25-74.9% aliphatic urethane acrylates, which can be cured quickly by UV/VIS irradiation, allowing for immediate application and exposure without solvent evaporation, and can withstand high temperatures and pressures, enabling thick layer holograms with high diffraction efficiency and stability.

Benefits of technology

Enables rapid production of thick holograms with high diffraction efficiency and stability, suitable for mass production, and eliminates the need for additional sealing, making them suitable for applications in head-up displays and augmented reality glasses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention relates to a photopolymerizable composition and an element made therefrom, and to the use thereof. The photopolymerizable composition is particularly suitable as a recording material for optical elements using refractive index modulation, particularly holograms.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a photopolymerizable composition and an element made therefrom, and to the use thereof. The photopolymerizable composition is particularly suitable as a recording material for optical elements using refractive index modulation, particularly holograms. [Background technology]

[0002] Many holograms are known, for example reflection holograms, embossing holograms, transmission holograms or volume holograms. For example, a volume hologram is created by interfering two light waves (also called object and reference waves) of the same wavelength and exposing a holographic recording medium (usually a photographic film) to generate interference fringes (usually a pattern of intensity). The hologram exposure process and hologram duplication (reproduction) are technically complex optical processes that require special application knowledge. The method of creating a hologram and its theory are described in detail in the following literature: Howard M. Smith, “Principles of Holography”, Wiley (1969); Fred Unterseher et al., “Holography Handbook: Making Holograms the Easy Way”, Ross Books (1982); Graham Saxby, “Practical Hologaphy”, Inst. of Physics Pub. (2004).

[0003] Known recording media with different performance profiles include silver halide emulsions, hardened dichromated gelatin, ferroelectric crystals, photochromic dichroid materials, and photopolymers [Howard M. Smith, “Principles of Holography”, Wiley (1969)]. For large volume applications, materials of interest are those that can be easily incorporated into hologram creation and replication devices to allow easy exposure and development of holograms. Photopolymers are considered particularly preferred, given their high efficiency, ease of handling, and good storage stability. The best-known photopolymer is, for example, Omnidex HRF 600, manufactured by DuPont [S.M. Schultz et al., “Volume grating preferential-order focusing waveguide coupler”, Opt. Lett., vol. 24, pp. 1708-1710, Dec. 1999]. Omnidex materials belong to a type of self-developing photosensitive polymer films based on radical polymerization and monomer diffusion (see EP 0 324 480 A2). Omnidex photopolymers have been further developed over the years, primarily to improve the refractive index contrast in the film and achieve high diffraction efficiency (see US Pat. No. 4,942,112A and DE Pat. No. 69,032,682T2). Nevertheless, well over two-thirds of the coating-related diffraction efficiency is provided by the high proportion of thermoplastic binder.

[0004] In the production of films, the binder for coating must be liquid. For this purpose, solvents are used, the evaporation of which leads to a rapid thinning of the layer thickness after coating. Depending on the solvent content, the applied wet layer is therefore significantly thicker than the resulting film layer. The solvent content is usually about 80%. In order to achieve a 20 μm layer that can be exposed by volume holography, a 100 μm wet layer must be applied in this case. The high thickness required for the wet layer makes known printing processes, such as flexographic or gravure printing, impossible or complicated. In screen printing, the use of fast-drying solvents can cause the meshes to stick to each other. Moreover, the film can only be further processed and wound up once the solvent has completely evaporated. Its production therefore requires the installation of long drying lines equipped with extraction systems that are health-conscious and environmentally friendly, while at the same time providing a dust- and explosion-proof environment. These difficulties mean that film production and hologram exposure are usually carried out in different locations and at different times.

[0005] In the case of binder-containing materials, post-treatment by heating ("annealing") of the exposed and UV-fixed photopolymer is also necessary to achieve maximum refractive index contrast (see DE 68905610T2). Annealing is an additional time-consuming processing step that slows, complicates and costs hologram production in addition to the time-consuming film preparation, and further limits the choice of substrate materials to those that are less temperature sensitive. Other photopolymer materials for volume holography are manufactured by Polaroid (see U.S. Pat. No. 5,759,721 A), Fujifilm (see European Patent Application Publication No. 1 510 862 A2), Konica Minolta Medical and Graphics (see U.S. Pat. No. 200505891 A1), Dai Nippon Printing (see European Patent Application Publication No. 123151 A1), Nippon Paint (see European Patent Application Publication No. 21 1615 A2), Nissan Chemical Industries, Ltd. (see U.S. Pat. No. 20050068594 A1), Bayer (see WO 2010091795 A1, Xetos (see WO 2003036389 A1), and InPhase. Technologies (see US Patent Publication No. 2002142227A1). The prior art features photopolymers that differ from Omnidex in their holographic performance or processing. The technological advances described are: reduced oxygen sensitivity, reduced shrinkage of the material upon exposure to light, spectral sensitivity, solvent-free film formation, high diffraction efficiency without annealing, and / or better temperature and storage stability.

[0006] A newer commercially available holographic photopolymer is the "Bayfol HX" film developed by Bayer Materialscience. It does not contain a thermoplastic binder, but instead contains polyurethane as the polymer matrix, which holds the holographically exposable write monomers. The polyurethane is formed by a polyaddition reaction of a polyisocyanate and a polyol mixture. The reactants are mixed together just before coating and cured on a carrier film. Although they do not have a high solvent content compared to the binder-containing materials mentioned above, the curing time of up to an hour presents the same problem of having to provide a sufficiently long, dust-free drying and curing section in the coating system. As with all commercially available photopolymer films, the user cannot choose and coat the carrier material of his own free will, but must process the film structure provided. In addition to the carrier film, there is also a laminating film on the light-sensitive film layer to prevent adhesion and contamination. When peeling this film, static electricity can be generated, which attracts dust particles. The film must be laminated to the glass or master for exposure, and since any dust particle will cause defects, an extremely dust-free environment is required for clean and defect-free processing.

[0007] Photopolymer systems that contain a polymeric binder or polymeric matrix form a substantially solid film layer. In contrast, binder-free systems that are substantially liquid until exposed to light have also been proposed (see, for example, U.S. Pat. No. 3,993,485 A, or N. Smirnova, "Optics in Information Systems", February 2004, p. 9, or Xetos (see WO 2003036389 A1)). In almost substantially solid monomer-binder / matrix photopolymers, the unexposed write monomers located in the areas of the dark interference lines diffuse into the exposed and polymerized areas after holographic laser exposure. This creates refractive index differences, the spatial modulation of which corresponds to the recorded interference fringes. However, the diffusion of the write monomers in the solid matrix takes time. This process can be accelerated by increasing the temperature. For the OmniDex® material mentioned above, DuPont specifies an annealing time of 1 hour at 120° C. For the Bayfol HX material, in its patent applications (EP 2 372 454 A1, p. 13,

[0127] ; EP 2 219 073 A1, p. 15,

[0102] ) specifies a waiting time of 5 minutes before the material is finally fully cured with UV light. However, when it comes to creating holograms, many creation processes require the shortest possible time or the highest possible throughput, and simple, cost-effective process control, making cumbersome and time-consuming post-processing and waiting times inconvenient. For this reason, photopolymerizable compositions have been developed which form an effective refractive index modulation already upon laser exposure and can be fixed immediately using UV light, as described in EP 1 779 196 B1, where various triglycerides, such as castor oil, have been used.

[0008] Castor oil is an inert ingredient and does not crosslink upon exposure to light, which means that it can later migrate out of the layer. To ensure this does not happen, a layer of UV varnish is usually then used to seal the holographic layer. However, if the castor oil content is too high, this can occur during or immediately after exposure. If the ratio is too high, turbidity also occurs. The higher the castor oil content, the higher the exposure temperature must be to ensure a clear layer. However, the higher the temperature, the lower the viscosity of the photopolymerizable composition, which is counterproductive to holographic exposure. Therefore, there is an upper limit for the castor oil content and exposure temperature, which must not be exceeded during holographic exposure.

[0009] In addition to the drawback that the exposed layer must be sealed relatively quickly with a UV varnish to prevent the castor oil from bleeding through, the photopolymerizable compositions have a relatively high turbidity: the thicker the layer and the higher the triglyceride content, the more noticeable the haze of the material. In the case of security elements and labels applied to opaque substrates, this is less noticeable. However, especially in the case of holographic optical elements (HOEs), an unobstructed field of view is desirable and often required, for example if the hologram is to be used in a head-up display or in augmented reality / mixed reality glasses. In contrast to security holographic elements, where very thin layers of less than 20 μm are desired, the layer thicknesses for HOEs can be much thicker and can range above 100 μm. With thick layers, it is often even desirable to compensate for the tolerances of the optical materials that are combined or bonded to the holographic layer. If only a very narrow spectral region of light is to be reflected, thick layers are often even required. However, liquid photopolymerizable compositions only form high refractive index differences up to a certain layer thickness, depending on their viscosity. Above a certain thickness, the dynamics of the liquid and the shrinkage upon curing are simply too great to effectively and homogeneously record patterns within the wavelength range of the light. This is especially true in the case of holographic dual-beam exposure or master exposure. In contrast, the large-scale production of substantially solid film materials with layer thicknesses of more than 20 μm is not worthwhile due to the extremely high costs and currently low demand. The Bayfol-HX 200 material from Covestro is available in a film thickness of 16 μm. Its haze value is specified as less than 2% (Product Information Sheet - Bayfol HX 200, version 2018-03-01).

[0010] In addition to the lowest possible haze value, holographic elements integrated into automobile windshields for head-up displays must also meet other requirements: During production, laminated glass is exposed to temperatures of 140° C. and pressures of 12 bar in autoclaves for up to 90 minutes (WO 03033583 A1). The holographic material and the holograms it contains must also withstand these conditions without damage or loss of quality. The diffraction efficiency ("Beugungswirkungsgrad" = BWG) η of volume holograms depends on their layer thickness d and Δn, where Δn represents the magnitude of the refractive index modulation inside the hologram layer. According to Kogelnik's coupled wave theory, the higher the value of Δn, the higher the BWG value can be achieved with a thinner layer (see H. Kogelnik, The Bell System Technical Journal, Volume 48, November 1969, Number 9, p. 2909-2947). For reflection holograms from a surface mirror or Lippmann-Bragg holograms, where the refractive index modulation is parallel to the surface, the following relationship holds:

number

[0011] With the photopolymerizable composition, both transmission and reflection holograms can be recorded. The achievable refractive index modulation Δn for Lippmann-Bragg holograms (whose grating lines run parallel to the surface) with a layer thickness of more than 100 μm is therefore greater than 0.001, preferably greater than 0.002, particularly preferably greater than 0.003. Using the wavelength λ from the absorption peak measured with a spectrometer under normal transmitted illumination, the diffraction efficiency η(BWG) and the layer thickness d, the Δn of the hologram can be calculated as follows:

number

[0012] [Figure 1] FIG. 1 is a schematic diagram of a roll-to-roll machine for making sealed holographic contact transfers from photopolymerizable compositions of the present invention. [Diagram 2] Schematic diagram of an exposure device. [Diagram 3] The path of the beam is shown. [Figure 4] Measurement curve at the corresponding measurement point of sample C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention is therefore based on the object of providing a photopolymerizable composition which avoids the disadvantages of known recording materials and advantageously allows holographic exposure of thick layers of more than 20 μm, preferably more than 50 μm, particularly preferably more than 100 μm. As with the liquid hologram materials known from EP 1 779 196 B1, it should be possible to process very quickly, suitable for mass production. The hologram elements made from the photopolymerizable composition should furthermore have high long-term storage, thermal and mechanical stability. Furthermore, additional sealing should be completely unnecessary. Particularly preferably, the cured material and the holograms recorded therein should also withstand the autoclave process for producing laminated glass without damage. Preferably, the photopolymerizable composition should be compatible with processes in which pressures of more than 5 bar and temperatures of more than 100° C., particularly preferably pressures of more than 10 bar and temperatures of more than 120° C., act on the photopolymerizable composition or the elements made therefrom. Surprisingly, it has been found that it is possible to advantageously replace inert ingredients such as castor oil in the formulations described in EP 1 779 196 B1 by suitable aliphatic urethane acrylates which also crosslink on exposure to light and therefore cannot be leached out. The object is therefore solved according to the invention by a photopolymerizable composition curable by irradiation with UV / VIS, comprising: a) from 25 to 74.9% by weight of at least one monomer M containing at least one ethylenically unsaturated group or a mixture of monomers comprising at least two monomers M and M1 containing different ethylenically unsaturated groups, b) 25 to 74.9% by weight of a single aliphatic urethane acrylate or a mixture of different aliphatic urethane acrylates; c) 0.1 to 10% by weight of a photoinitiator that activates the polymerization of those monomers and urethane acrylates upon exposure to actinic radiation; Here, the photopolymerizable composition is liquid at standard pressure in the range of 15°C to 150°C.

[0014] Weight percent numbers are based on the total weight of the photopolymerizable composition unless otherwise specified. Further preferred embodiments are defined in the dependent claims. Actinity (actinic radiation) is to be understood as the photochemical effect of electromagnetic radiation of various wavelengths. The term is used, for example, in assessing the physiological effects of laser light of various colors, or the spectral sensitivity of photographic film and paper. In photochemistry, an actinic chemical is one that is sensitive to the effects of light or radiation. Component a) preferably comprises more than 25% by weight, preferably more than 50% by weight, particularly preferably more than 90% by weight, of bisphenol A diacrylate, based on the total weight of component a).

[0015] Particularly preferred as component b) are aliphatic urethane diacrylate resins, in particular Ebecryl 230 (from Allnex), or difunctional aliphatic urethane diacrylate resins, in particular CN9002 (from Sartomer). The aliphatic urethane acrylate or mixture of urethane acrylates preferably has a much slower crosslinking rate than the monomer or mixture of monomers. During holographic exposure, the slower reacting components are driven out of the light areas of the interference fringes. Due to this separation, the urethane acrylate content is higher in the dark areas of the interference fringes than in the light areas. Since the urethane acrylate or mixture of urethane acrylates has a different refractive index than the monomer or mixture of monomers, the refractive index in the layer is modulated according to the interference fringes and a hologram is generated. The difference in refractive index of the two components should be at least 0.02, preferably at least 0.05, more preferably at least 0.07 at 20°C. It is preferred that the difference between the refractive index of component a) and the refractive index of component b) is at least 0.02 at 20°C. The refractive index can be measured using a refractometer, such as an analog Abbe refractometer.

[0016] The Abbe refractometer is an optical device for determining the refractive index n of liquids. Its measurement principle is based on the measurement of the critical angle for total internal reflection. For this purpose, the liquid is enclosed between two glass prisms and transilluminated with light of wavelength 589 nm (D line of sodium) as standard at a temperature of 20 °C. After setting the critical angle, the refractive index can be read off with the aid of the scale. The urethane acrylates are preferably reaction products of (meth)acrylic acid, polyols and polyfunctional isocyanates. They are prepared, for example, from alcohols containing (meth)acryloyl groups and di- or polyisocyanates. The processes for producing urethane acrylates are known in principle and are described, for example, in the following patents: DE-A-1 644 798, DE-A-2 115 373 or DE-A-2 737 406. Alcohols containing (meth)acryloyl groups are esters of acrylic acid or methacrylic acid with dihydric alcohols at the free hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 2- or 3-hydroxypropyl (meth)acrylate or 2-, 3-, 4-, hydroxybutyl (meth)acrylate, as well as various mixtures of such compounds. In addition, monohydric alcohols containing (meth)acryloyl groups or reaction products essentially consisting of such alcohols (those obtained by esterification of n-hydric alcohols with (meth)acrylic acid and any other dicarboxylic acid) are also possible, as is the use of mixtures of several alcohols as alcohol, where n is an integer or a fraction based on a statistical average value and is greater than 2 to 4, preferably 3, and in particular it is preferred to use (n-1) moles of (meth)acrylic acid per mole of the abovementioned alcohol.

[0017] Surprisingly, it has also been found that the clarity of an exposed layer depends on the exposure time and intensity used to expose or harden it. If a layer is exposed quickly, for less than 1 second, with sufficient intensity, it becomes less cloudy than if it is exposed for several seconds with a weaker input. The turbidity (haze) can be measured and expressed as a haze value in percent. The difference between the fast and slow exposed areas, measured according to the standard procedure of ASTM D1003, at an exposure temperature of 21° C. and a film thickness of 1 mm, should amount to at least 50%, preferably at least 60%, particularly preferably at least 70%. The temperature also influences the turbidity: the lower the temperature, the more milky the white color. In this way, exposing different areas at different temperatures can differentiate or even increase the intensity-dependent effect. The sensitivity of the photopolymerizable composition is 150 mJ / cm 2 Better, preferably 100 mJ / cm 2 Better, especially preferably 50 mJ / cm 2 Better is better.

[0018] The sensitivity represents the minimum radiation dose required to produce a hologram. The laser must have a wavelength that is matched to the dye used in the initiator system. For example, methylene blue is used when using a red laser with a wavelength of 633 nm, and safranine-O is used with a green laser with a wavelength of 532 nm. The laser wavelength should be close to the absorption maximum of the corresponding dye spectrum. The sensitivity can be determined by comparing the exposed holograms. The minimum required dose is reached or exceeded when, for the same layer thickness, increasing the radiation dose does not further improve the measured diffraction efficiency. It is preferred that the composition in the present invention does not require time for evaporation of volatile solvents, chemical reaction, or heat treatment after application to the substrate or copy master. Exposure can be performed immediately after application of the composition to the substrate or copy master. The wet application of the composition to the substrate can be performed by squeegee, doctor blade, or slot die coating. If the layer is thinner than 20 μm, known printing processes such as screen printing, gravure printing, intaglio printing, pad printing, or flexographic printing can also be used. It is preferred to directly laminate the photopolymerizable composition onto the master to be copied using a transparent and clear film. The layer thickness is controlled either by contact pressure and lamination speed or by slit width. When coating a thick and hard substrate, such as a glass plate, a spin-coating process can also be used. It is also possible to apply using an inkjet printing process or using a CNC-controlled dispersion device. It is also possible to directly inject into the cavity.

[0019] In particular, the photopolymerizable composition is also suitable for application to curved surfaces. It can also be used as a kit or adhesive by applying pressure between two counterparts. Since the coating is carried out in an exposure unit, the user has the freedom to choose the carrier material and the layer structure used. The photopolymerizable composition, which is substantially free of volatile organic solvents, preferably containing less than 5% by weight, more preferably at most 1% by weight, can be exposed immediately after application. According to the same principle, a new layer can be applied after curing and exposed holographically, so that it can also be used to build up true-colour holograms, for example from three layers for the primary colours red, green and blue.

[0020] Aliphatic urethane acrylates are preferred, as they have a relatively low reaction rate and high flexibility. The flexibility of the cured layer aids in the removal of the exposed hologram from hard surfaces, such as glass or metal. This easy and clean removal is highly favorable in mass production, since it allows the use of wear-free copy masters, such as conventional nickel shims, with fine holographic surface structures or volume holograms sealed with thin glass to create contact copies. The cleaning effort is kept low, as the non-adhesive layer is removed without leaving any residue. The photopolymerizable composition is particularly suitable for producing contact transfers. Due to the fact that the liquid photopolymerizable composition is printed directly onto the master, the need for refractive index matching is eliminated. This is because a liquid having approximately the same refractive index as the master and the holographic layer is applied between them. In conventional contact transfer methods using film materials, the refractive index matching prevents the occurrence of disturbing interference phenomena (Newton's rings) caused by reflections that occur in places where the two layers are not in close contact, for example due to dust inclusions or micro-irregularities resulting from air bubbles or air inclusions. In addition, the optical quality of the copy is improved because scratches and other irregularities on the substrate and master are compensated for. Microscopic dust particles, having dimensions smaller than the layer thickness, are embedded in the liquid and do not cause noticeable stains of the print or defects, as they do with film materials. This significantly reduces waste and the need for clean rooms in the production environment.

[0021] Therefore, the liquid photopolymerizable composition can advantageously also be used as an index match material for the exposure of holographic film materials. It does not need to be cleaned or evaporated to harden upon exposure. In addition, by combining the two hologram recording materials, the holographic recording is preserved and enhanced because holograms are created in both layers. Because the liquid material conforms to any surface, unlike film materials, it is possible to mold the surface structure simultaneously with the exposure of the hologram, allowing the use of surfaces with complex shapes. The surface structure can in particular be an embossed hologram or a Fresnel structure. This allows the physical and holographic duplication of both the surface structure and the volume holographic or optical information of the master in a single processing step. In this way it is also possible to create optical elements such as prisms or lenses, which have integrated holographic structures.

[0022] The photopolymerizable composition can be exposed immediately after coating, so that it is feasible to compact the distance and time between the two coating and exposure stations to a very short distance and time. This suppresses the risk of undesired pre-exposure caused by ambient light. Therefore, the need for a dark environment is not so great. The photopolymerizable composition can be coated and exposed within 1 minute, preferably within 20 seconds, and particularly preferably within 5 seconds. The present invention relates to a process in which the photopolymerizable composition according to the present invention is applied and exposed in less than one minute. The photopolymerizable composition in the present invention contains at least one monomer M containing at least one ethylenically unsaturated group, and preferably, monomer M contains at least two ethylenically unsaturated groups. Particularly preferably, the photopolymerizable composition comprises at least one monomer M containing at least one ethylenically unsaturated group and a monomer M1 containing at least two ethylenically unsaturated groups, where M1 preferably differs from M only in the second ethylenically unsaturated group. Monomers containing at least one ethylenically unsaturated group have the general structural unit:

[0023] [ka] During the ceremony,

[0024] [ka] (wherein n and m=0-12, preferably 1-12; o=0, 1, and Ar is a mononuclear or polynuclear, substituted or unsubstituted aromatic or heterocyclic aromatic group). The group R1 is H, methyl or ethyl, and The groups R2 and R3 are independently selected from the group consisting of alkyl, alkenyl, alkynyl, alkoxy, acyl, and acyloxy groups, which may be linear or branched, unsubstituted or substituted, substituted or unsubstituted aryloxy groups, substituted or unsubstituted aromatic or heterocyclic groups, unsubstituted or substituted alicyclic hydrocarbon groups, aliphatic, aromatic and aliphatic-aromatic amino, carboxylic acid, amido, and imido groups, hydroxy, amino, cyano, nitro, halogen atoms or hydrogen atoms, and combinations of the abovementioned groups, where the substituted groups are C1 to C6 12 Alkyl, C1-C 12 It may be substituted with alkoxy, hydroxy, carboxy, carbonyl, amino, amido, imido groups, halogen atoms, aromatic groups, or combinations thereof. Examples of suitable monomers M include: substituted or unsubstituted styrene monomers, acrylic acid, α-alkylacrylic acids, acrylic acid esters, α-alkylacrylic acid esters (whose alcohol component may be a substituted or unsubstituted aliphatic or aromatic group having 2 to 50 carbon atoms), acrylamides, α-alkylacrylamides (wherein alkyl is as defined above), vinyl esters, vinyl alcohols, vinyl ethers, and other substituted vinyl monomers substituted with substituted or unsubstituted aliphatic or aromatic groups having 2 to 50 carbon atoms.

[0025] Preferred examples of suitable monomers M include: (meth)acrylic acid butyl ester, (meth)acrylic acid phenyl ester, (meth)acrylic acid benzyl ester, (meth)acrylic acid isobornyl ester, (meth)acrylic acid cyclohexyl ester, (meth)acrylic acid 2-phenoxyethyl ester, (meth)acrylic acid 1H,1H,2H,2H-perfluorooctyl ester, (meth)acrylic acid 2,2,2-trifluoroethyl ester, (meth)acrylic acid heptafluoropropyl ester, (meth)acrylic acid 1,1,1,3,3,3-hexafluoroisopropyl ester, (meth)acrylic acid 2,2,3,3-tetrafluoropropyl ester, (meth)acrylic acid 2,2,3,3,4,4,4-heptafluorobutyl ... ,2,3,3,4,4,5,5-Octafluoropentyl, acrylic acid N,N-diethylaminoethyl ester, acrylic acid ethoxyethoxyethyl ester, acrylic acid 2-(p-chlorophenoxy)ethyl ester, p-chlorophenyl acrylate, 2-phenylethyl (meth)acrylate, pentachlorophenyl acrylate, phenyl acrylate, p-chlorostyrene, N-vinylcarbazole, 1-vinyl-2-pyrrolidone, 2-chlorostyrene, 2-bromostyrene, methoxystyrene, phenol ethoxylate acrylate, 2-(p-chlorophenoxy)ethyl acrylate, 2-(1-naphthyloxy)ethyl acrylate, hydroquinone monomethacrylate, and 2-[β-(N-carbazolyl)propionyloxy]ethyl acrylate.

[0026] Particularly preferred monomers M include N-vinylcarbazole, ethoxyethoxyethyl acrylate, 2-naphthyl acrylate, 2-phenoxyethyl acrylate, 2-phenoxyethyl methacrylate, phenol ethoxylate acrylate, 2-(p-chlorophenoxy)ethyl acrylate, p-chlorophenyl acrylate, phenyl acrylate, 2-phenylethyl acrylate, 2-(1-naphthyloxy)ethyl acrylate, t-butyl acrylate, isobornyl acrylate, cyclohexyl acrylate, N,N-diethylaminoethyl acrylate, acrylamide, ethoxyethoxyethyl acrylate, 1H,1H,2H,2H-perfluorooctyl methacrylate, and pentafluoroethyl acrylate. It is preferred that the monomer M contains at least two ethylenically unsaturated groups and therefore the monomer is preferably difunctional.

[0027] Difunctional ethylenically unsaturated monomers have two C=C double bonds in their molecule, i.e., they contain, for example, two of the structural units shown above. Difunctional ethylenically unsaturated monomers may, for example, contain two acrylate or methacrylate groups. The monomer M in the photopolymerizable composition of the present invention is preferably composed exclusively of one or more difunctional or higher functional monomers, i.e. the composition does not contain any monofunctional ethylenically unsaturated monomers. The content of the monomer M having at least two ethylenically unsaturated groups in the composition of the present invention is more than 10% by weight, preferably more than 20% by weight, particularly preferably more than 30% by weight, based on the total weight of the composition.

[0028] The use of difunctional or higher functional monomers in particular results in particularly high thermal and mechanical stability of the holographic elements produced therewith, which is particularly advantageous in the production of reflexion holograms. Preferred monomers M having at least two ethylenically unsaturated groups are ethoxylated bisphenol A diacrylates, specifically compounds of the formula: [ka] (wherein R1, Q. and Ar have the meanings given above).

[0029] Particularly preferred monomers M are compounds of the following structural formula: [ka] It is preferred that the viscosity of the monomer M or monomer mixture is at least 900 mPa·s at room temperature.

[0030] The photopolymerizable composition of the present invention contains a single aliphatic urethane acrylate or a mixture of multiple aliphatic urethane acrylates. Suitable urethane acrylates are generally compounds of the following general structural formula: [ka] (wherein R is a long chain polyol segment and NHCOO is a urethane compound.) Particularly preferred aliphatic urethane acrylates are the commercial products Ebecryl 230 (from Allnex) and CN 9002 (from Sartomer), and n1=0-1000, preferably 0-100, more preferably 1-12. The mixture of urethane acrylates contains one of the reaction products in an amount of 25%, preferably more than 50%, or, particularly preferably, contains only one of the two products.

[0031] The viscosity of the photopolymerizable composition is furthermore at least 2000 mPa·s, preferably at least 10000 mPa·s, particularly preferably at least 20000 mPa·s at 20°C. The viscosity can be measured using a plate-plate rotational rheometer (e.g., Haake, type 006-2805). The material is placed between two coaxial circular plates, one of which rotates. The distance between the plates is, for example, 1 mm, and the diameter is 35 mm. The viscosity can be determined from the measurement of the torque and the speed (e.g., 10 revolutions / second) (DIN 53018, ISO 3210).

[0032] The photopolymerizable composition according to the invention preferably comprises at least one photoinitiator, which upon exposure to (actinic) radiation activates the polymerization of the monomer M and the aliphatic urethane acrylate, and which is preferably a radical-forming polymerization initiator. Radical-forming polymerization initiators are known, see, for example, the following literature: HJ Timpe and S. Neuenfeld, "Dyes in Photoinitiator Systems", Kontakte (1990), pp. 28-35, and J. Jakubiak and JF Rabek, "Photoinitiators for visible light polymisation", Polymery (Warsaw) (1999), 44, pp. 447-461.

[0033] Suitable radical-forming polymerization initiators that can be activated by UV radiation and are generally inactive at temperatures up to 185° C. include substituted or unsubstituted polynuclear quinones, which are compounds having two ring carbon atoms in a conjugated carbocyclic ring system, such as 9,10-anthraquinone, 1-chloroanthraquinone, 2-chloroanthraquinone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, octamethylanthraquinone, 1,4-naphthoquinone, 9,10-furanthraquinone, 1,4-naphtho ... Phenanthrenequinone, 1,2-benzanthraquinone, 2,3-benzanthraquinone, 2-methyl-1,4-naphthoquinone, 2,3-dichloronaphthoquinone, 1,4-dimethylanthraquinone, 2,3-dimethylanthraquinone, 2-phenylanthraquinone, 2,3-diphenylanthraquinone, sodium salt of anthraquinone-α-sulfonic acid, 3-chloro-2-methylanthraquinone, lethenquinone, 7,8,9,10-tetrahydronaphthacenequinone, and 1,2,3,4-tetrahydrobenz[a]anthracene-7,12-dione. Other photoinitiators which are also useful (although some of them are thermally activated at temperatures as low as 85° C.) are described in U.S. Pat. No. 2,760,663 and include, for example, vicinal ketoaldonyl alcohols such as benzoin, pivaloin, acyloin ethers such as the methyl and ethyl ethers of benzoin, α-hydrocarbon-substituted aromatic acyloins such as α-methylbenzoin, α-allylbenzoin, and α-phenylbenzoin.

[0034] As photopolymerization initiators, the following can be used: photoreducible dyes and reducing agents, such as those disclosed in U.S. Pat. Nos. 2,850,445, 2,875,047, 3,097,096, 3,074,974, 3,097,097, 3,145,104, and 3,579,339; as well as phenazines, oxazines, and and dyes from the quinone class; Michler's ketone, benzophenone, 2,4,5-triphenylimidazolyl dimers with hydrogen donors, and mixtures thereof, as described in U.S. Pat. No. 3,427,161, U.S. Pat. No. 3,479,185, U.S. Pat. No. 3,549,367, U.S. Pat. No. 4,311,783, U.S. Pat. No. 4,622,286, and U.S. Pat. No. 3,784,557. A useful discussion of dye-sensitized photopolymerization can be found in D.F.Eaton, "Dye Sensitized Photopolymerization", Adv. in Photochemistry, vol. 13 (DH Volman, GS Hammond and K. Gollnick, eds, Wiley-Interscience, New York, 1986), p. 427-487. Similarly, the cyclohexadienone compounds of U.S. Pat. No. 4,341,860 are also useful as polymerization initiators.Suitable photoinitiators also include: CDM-HABI, i.e., 2-(o-chlorophenyl)-4,5-bis(m-methoxyphenyl)-imidazole dimer; o-Cl-HABI, i.e., 2,2'-bis(o-chlorophenyl)-4,4',5,5'-tetraphenyl-1,1'-biimidazole; and TCTM-HABI, i.e., 2,5-bis(o-chlorophenyl)-4-(3,4-dimethoxyphenyl)-1H-imidazole dimer, each typically used with a hydrogen donor, such as 2-mercaptobenzoxazole.

[0035] Particularly preferred photoinitiators are, for example, UV photoinitiators such as IRGACURE® OXE-01 (1,2-octanedione-1-[4-(phenylthio)-phenyl]-2-(O-benzoyloxime) and IRGACURE® OXE-02 (1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone-O-acetyloxime (BASF AG), as well as OMNIRAD-MBF (methylbenzoyl formate), OMNIRAD-TPO (2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide), OMNIRAD-TPO-L (ethyl-(2,4,6-trimethylbenzoyl)-phenylphosphinate), OMNIRAD-1173 (2-hydroxy-2-methyl-1-phenylpropanone), OMNIRAD OMNIRAD 1000 (a mixture of 2-hydroxy-2-methyl-1-phenylpropanone (80%) and 1-hydroxycyclohexyl-phenyl ketone (20%)), OMNIRAD 184 (1-hydroxycyclohexyl-phenyl ketone), OMNIRAD 819 (bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide), OMNIRAD 2022 (a mixture of 2-hydroxy-2-methyl-1-phenylpropanone, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and ethyl(2,4,6-trimethylbenzoyl)phenylphosphinate), and OMNICAT 440 (4,4'-dimethyl-diphenyl-iodonium-hexafluorophosphate), available from IGM Resins, are preferably used in an amount of 0.1 to 10% by weight.

[0036] [ka]

[0037] The above-mentioned photoinitiators may be used alone or in combination. Preferably, the photoinitiator includes a dye and a borate as a photoinitiator or co-photoinitiator. "Photoinitiator" and "co-photoinitiator" are used as the same term in the context of the present invention. Particularly preferred photoinitiators include compounds of formula I (co-photoinitiators) below and dyes (sensitizers) such as methylene blue, as well as the sensitizers disclosed in U.S. Pat. Nos. 3,554,753A, 3,563,750A, 3,563,751A, 3,647,467A, 3,652,275A, 4,162,162A, 4,268,667A, 4,454,218A, 4,535,052A, and 4,565,769A, as well as the dyes and co-photoinitiators cited in WO2012062655A2, which are expressly incorporated herein by reference. Particularly preferred sensitizers include DBC, 2,5-bis[(4-diethylamino-2-methylphenyl)methylene]cyclopentanone; DEAW, 2,5-bis[(4-diethylaminophenyl)methylene]cyclopentanone; dimethoxy-JDI, 2,3-dihydro-5,6-dimethoxy-2-[(2,3,6,7-tetrahydro-1H,5H-benzo[i,j]quinolizin-9-yl)methylene]-1H-inden-1-one; and Safranine O, 3,7-diamino-2,8-dimethyl-5-phenyl-phenazinium chloride.

[0038] The compound having structural formula I (developed by Ciba Specialty Chemicals Inc. under the product name "CGI 7460" and currently available from BASF AG under the product name SEC LCA 1460) is represented by the formula: [ka]

[0039] Particularly preferably, the dyes can be obtained in the form of a mixture free of volatile solvents as dye concentrates (see Tables 2 and 3), which simplifies the preparation of the photopolymerizable compositions, since evaporative removal of volatile substances is no longer necessary and metering becomes easier and more accurate. The dye in the photopolymerizable composition of the present invention is preferably selected from the group consisting of acriflavine, diaminoacridine, rhodamine B, safranine-O, diethylsafranine, and methylene blue. The co-photoinitiator in the photopolymerizable composition of the present invention is preferably selected from the group consisting of tetrabutylammonium tetrahexylborate, tetrabutylammonium triphenylhexylborate, tetrabutylammonium tris-(3-fluorophenyl)-hexylborate, and tetrabutylammonium tris-(3-chloro-4-methylphenyl)-hexylborate, or mixtures thereof.

[0040] The photoinitiator system that activates the polymerization of the monomers and urethane acrylates upon exposure to actinic radiation consists of a photoinitiator, or a co-photoinitiator and a dye, preferably containing all three of the above components. In order to adapt the photopolymerizable composition to a selected processing method or field of application and to improve printability, surface adhesion, viscosity, film-forming ability, flexibility, hardness, cold resistance, heat resistance, and weather resistance, the composition may contain various additives known per se. Thus, the photopolymerizable composition optionally includes additives.

[0041] Additives include; solvents, fillers, pigments, plasticizers, surfactants, common components used in photopolymer systems, polymeric binders, wetting agents, leveling agents, defoamers, adhesion promoters, surface additives, nanoscale particles, optical brighteners, or mixtures thereof. They should be easily mixed in and should not impair the diffraction efficiency. Non-volatile materials can permanently improve the diffraction efficiency in thin films, especially by choosing additives that increase the refractive index difference between the ethylenically unsaturated monomer and the other components of the photopolymerizable composition. If the urethane component has a lower refractive index than the ethylenically unsaturated monomer component, the additive should have a refractive index as low as possible. Therefore, in this case, known polymers with low refractive index, such as polyvinyl acetate, as well as fluorinated or silanized polymers are particularly suitable. In order to achieve good diffusion performance, the molecular weight of the additive considered should not be too high. The additives mentioned above and further described below can generally be used in an amount of 0.01 to 20% by weight, preferably 0.01 to 10% by weight, based on the total weight of the composition.

[0042] The photopolymerizable composition may include a plasticizer to enhance the modulation of the refractive index of the imaged composition. The plasticizer may be used in an amount ranging from about 0.01% to about 10% by weight, preferably from 5% to about 10% by weight, based on the total weight of the composition. Suitable plasticizers include triethylene glycol, triethylene glycol diacetate, triethylene glycol dipropionate, triethylene glycol dicaprylate, triethylene glycol dimethyl ether, triethylene glycol bis(2-ethylhexanoate), tetraethylene glycol diheptanoate, polyethylene glycol, polyethylene glycol methyl ether, isopropyl naphthalene, diisopropyl naphthalene, polypropylene glycol, glyceryl tributyrate, diethyl adipate, diethyl sebacinate, dibutyl suberinate, tributyl phosphate, tris(2-ethylhexyl) phosphate, Brij® 30 [C 12 H 25 (OCH2CH2)4OH], Brij® 35 [C 12 H 25 (OCH2CH2)20 OH], and n-butyl acetate. Particularly preferred plasticizers are: polyethylene glycol, triethylene glycol diethylhexanoate (3G8), triethylene glycol dicaprylate, tetraethylene glycol diheptanoate, diethyl adipate, Brij® 30, and tris(2-ethylhexyl) phosphate.

[0043] Other components commonly used in photopolymer systems may be used with the compositions and devices of the present invention, if desired. Such components include optical brighteners, ultraviolet light absorbing materials, heat stabilizers, hydrogen donors, oxygen scavengers, and release agents. These additives may further include polymers or copolymers. Useful optical brighteners include those disclosed in U.S. Patent No. 3,854,950A. A preferred optical brightener is 7-(4'-chloro-6'-diethylamino-1',3',5'-triazin-4'-yl)amino-3-phenylcoumarin. Ultraviolet absorbing materials useful in the present invention are also disclosed in U.S. Patent No. 3,854,950A.

[0044] Useful heat stabilizers include hydroquinone, phenidone, p-methoxyphenol, alkyl- and aryl-substituted hydroquinones and quinones, tert-butylcatechol, pyrogallol, copper resinate, naphthylamine, β-naphthol, copper(I) chloride, 2,6-di-tert-butyl-p-cresol, phenothiazine, pyridine, nitrobenzene, dinitrobenzene, p-toluquinone, and chloranil. Dinitroso-dimers, as described in U.S. Pat. No. 4,168,982A, are also useful. Typically, a thermal polymerization inhibitor is also present to improve the stability of the photopolymerizable composition during storage. Hydrogen donor compounds useful as chain transfer agents include 2-mercaptobenzoxazole, 2-mercaptobenzothioazole, and the like, as well as various types of compounds such as those disclosed in U.S. Pat. No. 3,390,996 A, column 12, lines 18-58, which are specifically incorporated herein by reference, such as (a) ethers, (b) esters, (c) alcohols, (d) compounds containing allylic or benzylic hydrogens, such as cumene, (e) acetals, (f) aldehydes, and (g) amides. Compounds which have been found to be useful as release agents are described in U.S. Patent No. 4,326,010 A. A preferred release agent is polycaprolactone.

[0045] The photopolymerizable composition may further comprise one or more polymeric binders selected from the group including: polymethyl methacrylate and polyethyl methacrylate, polyvinyl esters such as polyvinyl acetate, polyvinyl acetate / acrylate, polyvinyl acetate / methacrylate, and partially hydrolyzed polyvinyl acetate, ethylene / vinyl acetate copolymers, vinyl chloride / carboxylic acid ester copolymers, vinyl chloride / acrylic acid ester copolymers, polyvinyl butyral and polyvinyl formal, polymers and copolymers of butadiene and isoprene, and polyethylene oxides, epoxides containing acrylate or methacrylate residues, polystyrenes, cellulose esters, such as cellulose acetate, cellulose acetate succinate, and cellulose acetate butyrate, cellulose ethers, such as methyl cellulose and ethyl cellulose, polycondensates, such as polycarbonates, polyesters, polyamides, such as N-methoxymethyl polyhexamethylene adipamide, polyimides, polyurethanes, and the like, of polyglycols having an average molecular weight of about 1,000 to 1,000,000 g / mol. The above-mentioned polymeric binders can be used, for example, in an amount of 0.001 to 10% by weight, based on the total weight of the composition.

[0046] The photopolymerizable composition may further include one or more of the following: a wetting agent (e.g., a fluorocarbon polymer, such as Schwego-Fluor 8038™, or a fluorosurfactant, such as 3M Fluorad FC-4430™), a leveling agent (e.g., a glycolic acid n-butyl ester, or a polyether modified polydimethylsiloxane, such as ADDID 130™), a defoamer (e.g., a fluorosilicone oil based defoamer, such as ADDID 763™), an adhesion promoter (e.g., a diamino-trimethoxy functional silane adhesion promoter, such as ADDID 900™, or a glycidyl trimethoxy trifunctional silane coupling agent, such as ADDID 911™, vinyl triethoxy silane, or 3-methacryloxypropyl trimethoxy silane), or a surface additive (e.g., a polyether modified acryl functional polydimethylsiloxane, such as BYK-UV™). 3500™, polyether modified polydimethylsiloxanes such as BYK-UV 3510™, or polyether modified acryl functional polydimethylsiloxanes such as BYK-UV 3530™. Products bearing the trade names "ADDID" or "BYK" are available from Wacker Chemie and BYK Chemie, respectively. The photopolymerizable composition may further include nanoscale particles, such as TiO2, SiO2, or Au, which may be combined with the monomer (such materials are available, for example, under the trade name "Nanocryl").

[0047] Preferably, the additive can be an amine synergist, which in combination with other photoinitiators can increase the curing speed of UV coatings (see DE 60216490T2). Preferably, the additive can be a peroxide, which can be heat activated in combination with other photoinitiators to improve the curability of UV coatings, especially in shaded areas (see US Pat. No. 5,017,406 A or DE Pat. No. 6,003,023 T2). Preferably, the additive may be a marker selected from fluorescent pigments or lanthanide compounds, for example europium or terbium trisdipicolinate complexes may be used as lanthanide compounds.

[0048] For the purposes of the present invention, a marker is understood to be a forensically detectable entity that can be used to determine the authenticity or origin of a product or its manufacturer or distributor. It is also possible to introduce small individualised particles, coloured microplastics (known as forensically detectable additives), provided that the layer produced is thick enough to allow embedding the corresponding microparticles. It is preferred that the photopolymerizable composition is liquid at standard pressure and in the range of 20°C to 150°C, more preferably 25°C to 120°C.

[0049] In a further embodiment, the present invention includes an element comprising a component obtainable by exposing a photopolymerizable composition according to the present invention to (actinic) UV / VIS radiation. Preferably, the elements of the present invention include components having transparent and / or translucent regions. The photopolymerizable composition was exposed to a maximum of 50 mW / cm 2It can be made milky white by exposing it to a light source of at least 1 second to 5 minutes, preferably 2 seconds to 2 minutes. The result is a frosted screen whose scattering properties can be specifically and locally modified by the selected exposure method (time, intensity, temperature, etc.). A distinction can be made whether coherent laser light (speckles) or even white or UV light is used for exposure. The size of the speckles can be used to selectively adjust, for example, the granularity. The achievable resolution is extremely high. Therefore, it can preferably be provided with components that include transparent and / or translucent areas. Thus, using mask exposure it is possible to create a variety of structures, texts and images, which can be recognized via their matteness, independent of the holographic reproduction.

[0050] In a further embodiment the invention relates to the use of the element according to the invention as a film, lens, grating, prism, mirror, beam splitter, diffuser, surface relief, optical switch or sensor. By exposing with a directional beam and line pattern, it is possible to expose regularly spaced milky white lamellae vertically or diagonally in the layer, creating a louvre-like film that is transparent in the direction corresponding to the angle of exposure, but milky white otherwise. Such a film can be used, for example, as an eye protection film for a screen.

[0051] The whole can be combined with holographic properties by exposing the not yet exposed areas to light quickly and transparently in a holographic way. The film thus obtained is then made to react, for example, to illumination at a certain angle. Refraction and scattering of the beam can be coordinated. It is also conceivable to use several layers applied one after the other and exposed separately. In addition, it is possible to simultaneously mold surfaces, e.g. lens structures. In this way, for example, it is possible to create a structure that bundles the light from one LED array, makes it a directional beam, and reproduces other light from LEDs that are not in the lens array as scattered light. This scattering can be amplified by frosted areas outside the path of the lens beam. Using a honeycomb structure with frosted walls would also be a possible implementation.

[0052] One application would be a light source that emits direct, directional white-yellow sunlight with simultaneous scattered blue light to simulate a natural sky. This artificial "skylight" LED array could, of course, be further modified in brightness and color, as in the case of a screen, to simulate different lighting modes, times of day, overcast skies, moving clouds, etc. A reflection hologram could filter blue light from a directional white light beam and direct it towards a scattering center or surface. All of these, impressions, fluxing, scattering, and holograms, can be achieved with a polymerizable composition using a single exposure process or a combination of repeated coating and exposure in multiple layers.

[0053] Directional and diffuse light are also needed in automobiles: directional light for headlights to illuminate the road, and diffuse light for, for example, turn signals, brake lights, or reversing lights, to be visible to other road users over a wide angular range. By using certain films as listed and explained above, it would be possible to construct a headlamp, for example, so that it could also act as an indicator on the entire surface of the headlamp. The headlamp could emit directional headlamp light and, if necessary, at the same time, diffuse yellow light in all directions. Particularly preferred are elements according to the invention containing a hologram, obtainable by exposing a photopolymerizable composition according to the invention to modulated radiation carrying holographic information.

[0054] Holograms are generally made by exposing a layer of a photopolymerizable composition coated on a carrier substrate or a replica template to modulated radiation carrying the holographic information. The carrier substrate for making the elements of the present invention can be glass, plastic, especially PET, PP, PMMA, polycarbonate, or cellulose di- or triacetate, or paper. During exposure, the photopolymerizable composition can be, for example, placed between two glass plates. The present invention relates to a process for preparing an element according to the present invention or a photopolymerizable composition according to the present invention, in which the element or composition is subjected to a temperature higher than 100° C. and a pressure higher than 2 bar.

[0055] The present invention further relates to a method for forming a photostable hologram in a photopolymerizable layer on a substrate surface or copy master, comprising exposing a layer of the photopolymerizable composition of the present invention to modulated radiation containing holographic information. Particularly preferred are elements containing holograms, the holograms being treated with a swelling agent, which in the present invention is a means of diffusion and, in the case of reflection holograms, a substance which causes swelling of the hologram by spectrally shifting the reflected light to higher wavelengths. For example, a green reflective hologram can be converted to a red one. The same method can be used with a flashlight: the applied substance evaporates and penetrates the layer, just like a bolt of lightning. Surprisingly, this phenomenon occurs even when the photopolymer layer is already sealed by a layer of UV varnish.

[0056] Surprisingly, this can then be used to individualize the finished hologram. The swelling agent is applied, for example, using common inkjet printing methods. Due to a subsequent intense UV flash, the active substance evaporates and penetrates where it was applied, resulting in swelling and local color changes in the hologram. The introduced information can be, for example, an image, a number, an inscription. Since these changes are irreversible and only affect the hologram, this quick and simple process is a good way to advance the counterfeit prevention of ID cards, seals or vignettes. It should be easy to implement, especially for products that are individualized at the time of issue.

[0057] As an alternative to inkjet printers and flash, dye-sublimation printers can also be used, in which a swelling substance is evaporated by means of a suitable printer ribbon. In the case of thick layers, concentration gradients can occur, which cause the infiltrated material to swell more in the upper layers than in the deeper layers. This leads to a broadening of the absorption peak in the absorption spectrum. A double peak can also occur if the swelling region ends abruptly and the swelling intensity does not decrease gradually. A broadened peak means that a longer wavelength range is reflected, and that the reproduction angle at a certain wavelength becomes wider. The ability to subsequently change these important parameters of the hologram is useful in many technical applications, for example HUDs that must function over larger reproduction or viewing angles.

[0058] It is also possible to put the hologram layer in contact with a substance that contains a swelling agent. This can be, for example, a PVB film with a high content of a plasticizer, such as triethylene glycol diethylhexanoate (3G8). Depending on the swelling agent used and the layer applied to the hologram that contains and can release it, it is possible to vary its concentration as a function of temperature after diffusion into the hologram layer, since the diffusion equilibrium and the concentration gradient between the two layers are temperature dependent. With the shift of the absorption peak, the reproduction angle at a certain wavelength also changes, so that this reversible effect can be used as a sensor or optical switch. If this effect is undesirable, for example in laminated glass, the hologram can preferably be coated with a sealant, for example a UV varnish, which acts as a protective and barrier layer against diffusing substances. Particularly preferred is the use of the element according to the invention in head-up displays, laminated glass, data glasses, light guidance systems, spectrometers, detection systems, safety elements or labels. EXAMPLES

[0059] [Table 1]

[0060] The invention is explained in more detail below with the aid of examples. The compositions listed in Table 1 are known from the prior art.

[0061] [Table 2]

[0062] Such a composition is also known from EP 1 779 196 B1. Example of the present invention

[0063] [Table 3]

[0064] [Table 4]

[0065] [Table 5]

[0066] [Table 6]

[0067] The following photopolymerizable compositions were prepared from the monomer-containing mixtures and dye concentrates shown above for the exposure of samples A, B, and C. The known formulations listed in Table 1, omitting Safranin-O, were used as comparative examples. Dye concentrate FK2, containing methylene blue, was added to mixture A instead of Safranin-O. Samples D, E, and F were cured using only UV light, therefore only the UV photoinitiator Omnirad 1173 was added instead of the dye concentrate.

[0068] [Table 7]

[0069] [Table 8]

[0070] [Table 9]

[0071] [Table 10]

[0072] [Table 11]

[0073] [Table 12]

[0074] exposure [Table 13]

[0075] Photopolymerizable compositions A, B, and C were exposed to a laser having a wavelength of 577 nm at a temperature range of 20°C to 21°C. The photopolymerizable compositions were stored in an oven at 80°C and exposed immediately after coating. After laser exposure and UV curing, a spectrometer was used to determine the diffraction efficiency (BWG) based on the spectral absorption curve. The layer thickness was measured using a digital micrometer with the outside of the micrometer gauge. To demonstrate the exposure-dependent haze effect, samples D, E, and F were cured with a UV light source at various intensities. For fast curing, the UV bridge described above was again used. The samples were exposed for 30 seconds, although shorter times were sufficient to cure. For slower exposures, a Hamamatsu UV spot light source LC6 was used. The UV light was delivered at 3.5 W / cm at the end of a flexible light guide. 2 The samples were exposed for 120 seconds at a distance of 6 cm from the exit, after which they were safely post-cured for another 30 seconds under a UV bridge.

[0076] [Table 14]

[0077] The photopolymerizable compositions for UV exposure were kept at room temperature of 21° C. For the first exposure only, standard material D was kept and processed at 26° C. The second exposure at 21° C. with material D has a high haze value of 70% despite the rapid exposure, because at this temperature the liquid formulation is already milky white.

[0078] Exposure Configuration The laser beam, with a measured output of 1.43 W, was expanded horizontally using a polygon mirror scanner and focused by a cylindrical lens so that it covered an exposure width of 23 cm. Figure 2 shows a schematic of the exposure apparatus. References in Figure 2: 1 Laser 577nm 2. Mirror 3. Polygonal Scanner 4 Cylindrical Lenses 5 Scanning Beam 6 Scanner Mirror Each sample was exposed to light by scanning this line with a moving mirror. The moving speed was set at 9 mm / sec. The laser beam struck the sample surface at an angle of 22 degrees to the normal.

[0079] The beam path is shown in FIG. References in Figure 3: 1 Scanning beam 577nm 2 Scanner Mirror 3 Exposure direction 4 Exposure angle, 22 degrees 5 Substrate, glass or foil 6. Photosensitive polymers (photopolymerizable compositions) 7 Master plate, mirror plate To create a reflection hologram, a sample material is applied to a mirror plate that reflects laser light. Interference between the incident and reflected beams creates a line pattern of bright and dark spots parallel to the mirror's surface. This interference pattern is recorded in the object in the form of refractive index modulation, creating a so-called Lippmann-Bragg hologram.

[0080] When using laser exposure, the photopolymer layer is between the mirror plate and a transparent substrate, e.g., a PET film or glass. In these examples, a glass substrate was used as the target. The glass was used to cover the droplets applied to the mirror plate. The layer thickness is determined by the amount of the droplet and the spread of the droplet. The size of the circular spread can be adjusted with the contact pressure, temperature, and flow time. It is also possible to use spacers to achieve the desired layer thickness. After laser exposure, the material is cured using UV light. In the first curing step, we use a UV flash with a power of 3000WS. This is enough to remove the hologram together with the carrier from the plate. To ensure adhesion to the glass, a pretreatment with a primer should be done. To finally cure the samples, we use a UV bridge with an arc length of 70 mm and a power output of 120 W / cm, with an exposure time of 30 seconds.

[0081] Measuring Equipment The samples were measured in transmitted light using a spectrometer (CAS 140B, Instrument Systems). This was done with perpendicular illumination. At this point, the spectral curve shows a clear absorption peak, since the hologram reflects only those wavelengths that satisfy the Bragg condition. Peak value T Peak and the reference value T of the upper baseline in the neighborhood Ref From this, the diffraction efficiency (BWG) η is calculated as follows: η = (T Ref -T Peak ) / T Ref

[0082] FIG. 4 shows the measurement curves of sample C at the corresponding measurement points. The exposure table values ​​(Table 12) show that all samples achieve diffraction efficiencies higher than 80% at layer thicknesses above 100 μm. Even higher values ​​are achieved for the exposure of the photopolymerizable compositions B and C according to the invention than for the comparative mixture A. The haze values ​​of UV-exposed samples D, E and F were measured according to the standard procedure of ASTM D1003 with a haze meter (haze-gard i, manufactured by BYK) using a 4 mm aperture. The tabulated values ​​(Table 13) show that different turbidities are achieved by varying the exposure intensity. With a layer thickness of about 0.9 mm, the difference can be more than 70%. The two measurements of comparative sample D show that the exposure temperature also has an effect. In contrast to the inventive compositions E and F, the liquid comparative mixture D is not clear at 21°C.

[0083] create FIG. 1 shows a schematic configuration of a compact roll-to-roll machine for making sealed holographic contact transfers from the presently claimed photopolymerizable compositions. [Explanation of symbols]

[0084] References in Figure 1: 1. Storage container 2. Filters and deaerators 3 Dosing unit 4 Supporting foil 5. Photosensitive polymers (photopolymerizable compositions) 6 Supporting foil with hologram 7 Unrolling the foil 8. Laser Light 9 Original version 10 UV light 11 Foil winder

Claims

1. 1. A photopolymerizable composition curable by UV / VIS radiation, comprising: a) from 25 to 74.9% by weight of at least one monomer M containing at least one ethylenically unsaturated group or a mixture of monomers containing at least two monomers M containing different ethylenically unsaturated groups b) 25 to 74.9% by weight of a single aliphatic urethane acrylate or a mixture of different aliphatic urethane acrylates; c) 0.1 to 10% by weight of a photoinitiator that activates polymerization of the monomers and urethane acrylate upon exposure to actinic radiation; Including, the photopolymerizable composition is liquid at a temperature in the range of 15° C. to 150° C. under standard pressure and is suitable as a recording material for an optical element with refractive index modulation; the photopolymerization initiator comprises a dye and a borate as a copolymerization initiator; Component a) comprises bisphenol A diacrylate in an amount greater than 25% by weight, based on the total weight of component a); Photopolymerizable composition.

2. 2. The photopolymerizable composition of claim 1, wherein the difference between the refractive index of component a) and the refractive index of component b) at 20[deg.] C. is at least 0.

02.

3. 3. The photopolymerizable composition of claim 1, wherein the copolymerization initiator is selected from the group consisting of tetrabutylammonium tetrahexylborate, tetrabutylammonium triphenylhexylborate, tetrabutylammonium tris-(3-fluorophenyl)-hexylborate, and tetrabutylammonium tris-(3-chloro-4-methylphenyl)-hexylborate, or a mixture thereof.

4. The photopolymerizable composition according to any one of claims 1 to 3, wherein the photopolymerizable composition has a viscosity at 20°C of at least 2000 mPa·s.

5. The photopolymerizable composition according to any one of claims 1 to 4, wherein component b) is an aliphatic urethane diacrylate resin or a difunctional aliphatic urethane diacrylate resin.

6. An element comprising a component obtained by exposing the photopolymerizable composition according to any one of claims 1 to 5 to UV / VIS radiation, preferably to actinic UV / VIS radiation.

7. 7. The device of claim 6, comprising a component having transparent and / or translucent regions.

8. 8. An element according to claim 6 or 7, comprising a hologram obtainable by exposing a photopolymerizable composition according to any one of claims 1 to 5 to modulated radiation carrying holographic information.

9. Use of the element according to any one of claims 6 to 8 as a film, lens, grating, prism, mirror, beam splitter, diffuser, surface relief, optical switch or sensor.

10. Use of the element according to any one of claims 6 to 8 for a head-up display, a laminated glass, a data glass, a light guidance system, a spectrometer, a detection system, a safety element or a label.

11. A process for preparing an element according to any one of claims 6 to 8 or a photopolymerizable composition according to any one of claims 1 to 5, wherein said element or composition is subjected to a temperature higher than 100°C and a pressure higher than 2 bar.

12. A method for forming a photostable hologram in a photopolymerizable layer on a substrate surface or copy master, comprising exposing a layer of the photopolymerizable composition of any one of claims 1 to 5 to modulated radiation carrying holographic information.

13. A process comprising applying the photopolymerizable composition of any one of claims 1 to 5 and exposing for less than 1 minute.